A new species of the genus Megatachycines (Rhaphidophoridae: Aemodogryllinae: Aemodogryllini) from Guizhou, China - Yin, Kesong; Xiao, Yunxue; Luo, Changqing (Zootaxa, 2022)
Zhu et al. (2022) proposed the genus Megatachycines based on the description of a new species and the reviewed genus Microtachycines. In this study, a new species of Megatachycines, namely Megatachycines rectangularis sp. nov., from Guizhou Province, China is described. This new species is similar to Megatachycines elongatus, and the morphological differentiation between the two species is discussed. Morphological information including diagnosis of the new species, description of male genitalia, and some related photographs of males and females are provided.